Product Market Interventions and Stock Returns : Evidence from Automobile Manufacturing Firms from India - Joshi, Himanshu (Indian Journal of Research in Capital Markets, 2019)
The present paper investigated the impact of product market interventions related to new product announcement, new product launch, and product withdrawal on firms’ stock returns using 10 year time series data for a cross section of Indian automobile firms. The multiple regression model was used to establish the impact of marketing initiatives on firms’ stock returns. The results showed that all the three market interventions, that is, product announcement, product launch, and product withdrawal significantly affected firms’ stock returns for all the firms under the subcategories of commercial vehicles and passenger car manufacturers. However, for two wheeler firms, only product announcement and product launch were found to be statistically significant, but not product withdrawal. This study has valuable implications for two set of stakeholders of firms, namely equity investors and firms’ marketing managers. From the equity investors’ point of view, the study identified important qualitative variables to examine and predict stock returns beyond the traditional financial metrics. These are new product announcement, product launch, and product withdrawals. For firms’ marketing managers, the study confirmed that the capital markets considered firms’ product market initiatives as strategic decisions and responded positively to new product announcement and product launch and negatively to product withdrawals.